PENYULUHAN TENTANG PERAN ORANG TUA DALAM POLA ASUH ANAK MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2014 DI KECAMATAN GANTAR - Abdur Rahim; Annisa Azzahra; Shakira Nurul Sakinah; Ikhfi Khoirunnisa; Ali Sodikin; Cahyadi Cahyadi; Warji Warji; Muhammad Haikal Fadillah (LPPM Universitas Bina Bangsa, 2023)
Counseling is an educational activity, providing knowledge, or information that has not been obtained by the community. With the existence of counseling activities about the role of parents in child care according to Law Number 35 of 2014 in Gantar District to the community, both parents and children, which aims to produce prospective successors of the nation who are useful for advancing the nation, because not only parents who serve an important role in the family, children also have a very important role in accordance with Law Number 35 of 2014. As for the counseling activities that we carry out using methods carried out through Surveys, Facto Exposes, and Descriptive. The result of this activity is that the role of parents is regulated by Article 26 paragraph (1) of Law Number 35 of 2014 which states that parents are responsible for raising, nurturing, educating and protecting children. Aspects of child development that require parental guidance is the development of social-emotional behavior. Most parents are very rarely aware of the close relationship between social-emotional behavior of children with success and happiness in childhood and later life. By carrying out this activity, we can explain how important the role of parents is in development and growth. We can participate by providing knowledge that can make all parents aware that children are a gift from God, which must be looked after, guided with love